Fruit Powder as Natural Preservatives for Raw Chevon - Mahapatra, G.; Biswas, S. (International Journal of Bio-resource and Stress Management, 2019)
Meat has high moisture content and is a rich source nutrients, making it vulnerable to spoilage. Meat preservation is largely based on chemical preservatives but prolonged intake of such chemicals may be hazardous to human health. This study focuses on utilization of fruit powders as meat preservatives. Starfruit (Averrhoa carambola) and guava (Psidium guajava) powder were added to raw minced chevon at the rate of 1.0%, 1.5% and 2.0% on w/w basis. The preservation effect of these additives on chevon stored at refrigeration temperature (4±1 °C) was determined by analyzing the effect of these powders on the lipid oxidation rate and microbial quality. For determining the rate of lipid-oxidation thiobarbituric acid reacting substances (TBARS) value was determined whereas to determine the microbial quality of meat total plate count (TPC), total psychrotrophic count (TPSC), total coliform count (TCC) and yeast and mouldcount (YMC) were determined. These studies were conducted on 0,3,7,14 and 21 day of refrigerated storage. Compared to control, the starfruit and guava powder treated samples had significantly lower(p<0.05) TBARS values hence indicated delayed development of rancidity extending the shelf-life from 14 to 21 days of refrigerated storage. Similarly, the fruit powder treated samples had significantly lowered (p<0.05) total plate count and total psychrotrophic count increasing the shelf-life to 7 days of refrigerated storage. The fruit powders were capable of inhibiting coliform and yeast and mould growth till the 3rd day of refrigerated storage. Hence, it could be inferred that both starfruit and guava powder can successfully be utilized as natural preservative for minced chevon storage.